Fertilidade do sêmen eqüino diluído, resfriado e transportado - Da Silva Filho, José Monteiro; Fonseca, Francisco Aloízio; Palhares, Maristela Silveira; Oliveira, Henrique Nunes [UNESP] (My University, 1997)
The objetive of this experiment was to study the effect of semen transportation conditions on the fertility of inseminated mares. Seventy-six Mangalarga Marchador mares were allocated in a completely randomized design experiment with different number of replications to compare the following conditions: raw semen, transported or not and transported cooled diluted semen. The semen was diluted in a lactose-egg yolk extender without glycerine. The mares were inseminated, every other day, using semen of only one stallion. The inseminating volumes varied according to the number of mares to be inseminated on the same day, using only one ejaculate. Semen transportation was provided by a special container (MSP-1), projected for this objective. There were no differences among treatments for the following variables analized: conception rate/first cycle, total conception rate, efficiency of pregnancy, number of cycles/mare, cycles/pregnant mare, cycles/pregnancy, pregnancy/cycle, number of inseminations/mare, inseminations/pregnant mare and number of inseminations/open mare. The modified lactose-egg yolk extender without glycerine, can be recommended for dilution of cooled semen to be transported. In this case and covering a short distance and a short period of time a good extender is more important than a sophisticated transport container.
Fertility of diluted, cooled and transported equine semen
Keywords: Artificial insemination; Cooled semen; Equine; Transported semen